Is density- dependent prophylaxis transmitted to offspring? Experiments with Anticarsia gemmatalis (Lepidoptera: Noctuidae) - Viol, Daniel Luis (2015)
Animals and disease-causing microorganisms are in a constant fight. While pathogens evolve ways to breach the host defences, hosts enhance defences to prevent the establishment of diseases. Not only individuals themselves, but populations may be affected by pathogens. Thus, organisms have mechanisms to avoid infectious processes through perception of environmental clues. The increase in population density of conspecifics may be such a clue, and individuals able to perceiving it could increase plastically the investment in immune defences; hypothesis known as ‘Density- dependent prophylaxis’ (DDP). Furthermore, organisms may invest plastically in defences of offspring via epigenetic. It is known that immune defences pose a high cost to hosts, and the use of the two strategies – DDP and transgenerational transfer – could optimize the prevention of disease in organisms subject to population fluctuation and likely overlap of generations, such as insect pests. Anticarsia gemmatalis is known to be a lone-living insect, but presents density-dependent plasticity in phenotype as such group-living insects. Thus, A. gemmatalis was chosen as model to test if there is transgenerational transfer of DDP. It was assessed the antimicrobial activity (lysozyme- like activity), through inhibition zone in plates with the bacterium Micrococcus lysodeikticus, in eggs of moths from different phenotypes (i.e. caterpillars were raised alone or in groups and expressed green or black phenotype, respectively). Moths were paired in cages in four possible combinations between females and males expressing “green” or “black” phenotypes. Thus, it was possible to identify the contribution of each partner in the provision of immune defence to offspring. Furthermore, it was assessed the number of eggs per female as a way to find out likely trade offs between immunity and reproduction. There were no significant differences in antimicrobial activity neither in the number of eggs from moths of green or black phenotype. These results indicate that, at least for the immune defence assessed here, there is no transgenerational transfer of DDP to offspring. As this is a migratory species, maybe the offspring do not experience the same environmental conditions of the parents; hence they do not transfer immune defences to offspring by stimuli experienced by parents. It is proposed to investigate the transfer of DDP in other larval instars of offspring, through the assessing of different immune parameters, to better support our conclusion.